Cardiospermum corindum L. (Sapindaceae): A New Record for the Flora of Nepal - Chalise, Pratikshya; Dhakal , Sajita; Paneru, Yagya Raj (Journal of Plant Resources, 2024)
Cardiospermum corindum L. (Sapindaceae), is reported as a new addition to the Flora of Nepal. A brief description, keys, photograph of a herbarium specimen and distribution of the species are provided.